All’ombra di nuove scienze in fiore. Lo strano caso della cibernetica con uno sguardo all’Italia degli anni Sessanta - Termini, Settimo (Philosophy Kitchen - Rivista di filosofia contemporanea, 2023)
The present paper describes and discusses certain aspects of the evolution of cybernetics, with a focus on the Italian context. It considers the ways in which cybernetic questions relate to present issues of crucial importance. The aim will be to interpret cybernetics as an unfinished and interdisciplinary scientific paradigm, reflecting on the contribution represented by this specificity. Reference will be made to the figure of the Italian cyberneticist Eduardo Caianiello as a paradigmatic case.